Analysis of Diagnosis and Treatment for Perianal Necrotizing Fasciitis with Integrated Traditional Chinese and Western Medicine - Li, Zongde; Wang, Yu; Hu, Di; Lai, Xiangquan (Journal of Contemporary Medical Practice, 2025)
Objective: Through a retrospective analysis of 21 cases of necrotizing fasciitis in the Department of Anorectal Medicine at the First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, this study aims to deepen the understanding of clinical diagnosis and treatment for patients with necrotizing fasciitis and improve the clinical cure rate. Methods: Clinical data of 21 patients with perianal necrotizing fasciitis admitted to the Department of Anorectal Medicine at the First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine from December 2022 to December 2023 were collected and subjected to in-depth statistical analysis. The study summarized and analyzed potential risk factors for early necrotizing fasciitis, main pathogenic bacteria causing infection, adopted treatment methods, and final therapeutic effects. Results: After integrated traditional Chinese and Western medicine treatment, all 21 patients showed significant improvement in their conditions and were successfully discharged. The average hospital stay was 18.95 days, providing important reference for the treatment cycle of this disease. Conclusions: 1) Early comprehensive evaluation of patients’ conditions and timely surgical debridement and drainage are key measures for treating perianal necrotizing fasciitis, which are crucial for controlling disease progression and preventing deterioration; 2) Diabetes is the most common risk factor for perianal necrotizing fasciitis; 3) Gram-negative bacteria are the predominant pathogenic bacteria; 4) Nursing care for postoperative wound dressing changes is an important guarantee for prognosis; 5) Traditional Chinese medicine plays a significant role in the treatment of necrotizing fasciitis, with oral and external applications applied throughout the treatment process and precise intervention based on disease stages. Integrated traditional Chinese and Western medicine treatment combines the advantages of both to enhance therapeutic effects.